Effectiveness and safety of endothelin receptor antagonists, alone and in combination therapy, in the pulmonary arterial hypertension‐connective tissue disease subtype: A systematic review and meta‐analysis. (21st July 2020) - Shivakumar, Senthuran; Thynne, Tilenka R.; Mohammadi, Leila; Burdeniuk, Christine; Mangoni, Arduino A.
Abstract: Introduction: There is limited information regarding the effectiveness of endothelin receptor antagonists (ERA) in patients with connective tissue disease‐pulmonary arterial hypertension (CTD‐PAH), a condition that is characterized by poorer clinical outcomes compared to other PAH subtypes. Objective: To conduct a systematic review and meta‐analysis of the effectiveness and safety of ERA in CTD‐PAH. Methods: A literature search, using MEDLINE, COCHRANE, CINAHL and EMBASE databases was conducted, from inception to May 2019 to identify randomized control studies of ERA, as monotherapy or in combination with phosphodiesterase type 5 inhibitors (PDE5i), in CTD‐PAH. A protocol was registered in PROSPERO (CRD42019136956). Efficacy outcomes, including the 6‐minute walk distance (6MWD) and composite clinical failure endpoints (CFE), and safety outcomes were evaluated. Results: A total of 13 studies, including 784 CTD‐PAH participants, were identified. ERA, as monotherapy, did not reduce the risk of CFE compared to placebo (odds ratio [OR] 0.77, 95% CI 0.50‐1.19, P = .25). By contrast, combination therapy (ERA + PDE5i) significantly reduced the risk of developing CFE vs monotherapy (OR 0.54, 95% CI 0.32‐0.90, P = .02). 6MWD did not improve when comparing monotherapy vs placebo (+17.41 m; 95% CI −19.83‐54.66) P = .36) or combination therapy vs monotherapy (+13.17 m; 95% CI −16.44‐42.78, P = .38). ERA‐related adverse events rates in CTD‐PAH and general PAH cohorts were comparable. Conclusions: ERA, when used in combination with PDE5is, are associated with reduced risk of CFE, but no significant changes in 6MWD, in CTD‐PAH. This warrants further studies investigating early combination therapy as a standard of care in this group.